Securing Peace State-building and Economic Development in Post-conflict Countries - Kozul-Wright, Richard; Fortunato, Piergiuseppe (The United Nations Series on Development, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. This book studies the processes which lead to explosion of civil strife and tries to spell out the policy options available to address the challenges faced by post-conflict economies. It calls for a more integrated policy approach which can gradually repair trust in public institutions as it addresses the vulnerabilities and grievances that helped start the process. Usually, such societies do not have the luxury of meeting the goals of security, reconciliation and development in a measured or sequenced manner: to avoid an immediate return to violence they must begin the recovery process on all fronts simultaneously.